1999
DOI: 10.1088/0022-3727/32/16/310
|View full text |Cite
|
Sign up to set email alerts
|

Excitation theory for space-dispersive active media waveguides

Abstract: Abstract.A unified electrodynamic approach to the guided-wave excitation theory is generalized to the waveguiding structures containing a hypothetical space-dispersive medium with drifting charge carriers possessing simultaneously elastic, piezoelectric and magnetic properties. Substantial features of our electrodynamic approach are: (i) the allowance for medium losses and (ii) the separation of potential fields peculiar to the slow quasi-static waves which propagate in such active media independently of the f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In order to incorporate these interactions, the magnetic eld, H, is replaced by an e ective magnetic eld, H e , that includes other torque-producing contributions besides the external magnetic eld. The e ective magnetic eld can be modeled in the following way [3,8,27] H e = H + H an + H ex + H me (3.9) where the di erent terms are: 1) the classical magnetic eld, H, appearing in Maxwell's equations 2) the crystal anisotropy eld H an = −N c · M due to magnetocrystalline anisotropy of a ferro-or ferrimagnetic material, 3) the exchange eld H ex = λ ex ∇ 2 M due to non-uniform exchange interaction of the precessing spins 4) the magnetoelastic eld H me due to interaction between the magnetization and the mechanical strain of the lattice. The anisotropy tensor N c is assumed to be known, as well as the exchange constant λ ex .…”
Section: Microscopic Origin and Modeling Of Magnetic Lossesmentioning
confidence: 99%
“…In order to incorporate these interactions, the magnetic eld, H, is replaced by an e ective magnetic eld, H e , that includes other torque-producing contributions besides the external magnetic eld. The e ective magnetic eld can be modeled in the following way [3,8,27] H e = H + H an + H ex + H me (3.9) where the di erent terms are: 1) the classical magnetic eld, H, appearing in Maxwell's equations 2) the crystal anisotropy eld H an = −N c · M due to magnetocrystalline anisotropy of a ferro-or ferrimagnetic material, 3) the exchange eld H ex = λ ex ∇ 2 M due to non-uniform exchange interaction of the precessing spins 4) the magnetoelastic eld H me due to interaction between the magnetization and the mechanical strain of the lattice. The anisotropy tensor N c is assumed to be known, as well as the exchange constant λ ex .…”
Section: Microscopic Origin and Modeling Of Magnetic Lossesmentioning
confidence: 99%
“…The field H is the classical magnetic field, which is the one appearing in Maxwell's equations, whereas the remaining fields are of microscopic (quantum mechanical) origin. The magnetocrystalline anisotropy field H an is due to the atomic lattice and can, to first order, be modelled with a symmetric tensor N c as H an = −N c M [19]. The exchange field H ex is due to the nonuniformity of the magnetization and can be modelled as [20].…”
Section: Equation Of Motionmentioning
confidence: 99%
“…Here j l (k ln r) denote the spherical Bessel functions and Y lm (θ, φ) are the spherical harmonics. Assuming that the magnetic field H 1 is uniform, inserting (19) into (17) and using the orthogonality of the M 1,nlm functions, it can be shown that all mode coefficients are zero for indices l, m = 0, and that the remaining ones are where M ± 1 = (x ± iŷ)/ √ 2, and x ln = k ln R are the roots of…”
Section: Excitation Of Exchange Modesmentioning
confidence: 99%
“…Application of reciprocity theorem and mutual energy theorem can also be found in the examples [26][27][28][29]. There are a few reference discussed the relationship between Poynting theorem and reciprocity theorem [30][31][32].…”
Section: Introductionmentioning
confidence: 99%